2017
DOI: 10.1007/s10853-017-0766-6
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of ketorolac tromethamine (KTC) using Ag-doped ZnO microplates

Abstract: In this study, Ag-doped ZnO microplates were prepared via precipitation technique and further characterized by FESEM, EDS, XRD, FTIR, TGA, XPS, UV-DRS and RT-PL techniques. The outcomes indicated that Ag + ions were well incorporated into ZnO lattice leading to the absorption of ZnO in visible region as well as effective charge separation. The photocatalytic experiments showed that Ag-doped ZnO microplates show higher catalytic activity (91%) than bare ZnO (71%) for the degradation of KTC drug under solar illu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 52 publications
1
8
0
Order By: Relevance
“…This curve could be deconvoluted into the above-mentioned three oxidized states with an additional weak peak at 528.9 eV (denoted as O IV ). As indicated in the previous reports [ 39 , 40 , 41 ], this oxidized state observed only in the Ag-ZnO co-sputtered film was the contribution of the atomic oxygen with an ionic Ag-O bond, which implied the activated Ag dopants (Ag Zn ) as a substitution for the lattice Zn in the ZnO matrix. Additionally, in agreement with [ 21 ], the incorporation of the Ag atoms in the ZnO film also led to the reduction in the oxygen vacancy-related defects as evidence of the decrease in the ratio of the peak area (O II /(O I + O II + O IV )).…”
Section: Resultssupporting
confidence: 60%
“…This curve could be deconvoluted into the above-mentioned three oxidized states with an additional weak peak at 528.9 eV (denoted as O IV ). As indicated in the previous reports [ 39 , 40 , 41 ], this oxidized state observed only in the Ag-ZnO co-sputtered film was the contribution of the atomic oxygen with an ionic Ag-O bond, which implied the activated Ag dopants (Ag Zn ) as a substitution for the lattice Zn in the ZnO matrix. Additionally, in agreement with [ 21 ], the incorporation of the Ag atoms in the ZnO film also led to the reduction in the oxygen vacancy-related defects as evidence of the decrease in the ratio of the peak area (O II /(O I + O II + O IV )).…”
Section: Resultssupporting
confidence: 60%
“…As seen in Figure 6 , the XPS analysis was carried out to investigate the nanoparticle composition. In Figure 6 a, it was observed that the binding energy regions positioned at 1022 eV and 1045 eV were assigned to Zn 2p 3/2 and Zn 2p 1/2 , respectively [ 51 ], from the spectrum lines of both of the ZnO-MCM-3 and ZnO-MCM-9. Zn/Sal-MCM-3 and Zn/Sal-MCM-9 showed two peaks of Zn 2p at 1021 eV and 1044 eV, respectively, which means that the zinc ions were coordinated with salicylaldimine.…”
Section: Resultsmentioning
confidence: 99%
“…The phase and structural properties of as-prepared ZnO and Ag/Fe 2 O 3 /ZnO were investigated by XRD analysis (Figure 1a). The diffraction peaks obtained at 2θ = 31.85 101), ( 102), ( 110), ( 103), ( 200), ( 112), ( 201) and (202) lattice planes of the standard pattern of the wurtzite hexagonal phase of ZnO (JCPDS 36-1451), respectively [65,66].…”
Section: Characterization Of Prepared Ag/fe 2 O 3 /Zno Samplementioning
confidence: 99%